Unexpectedly high leprosy seroprevalence detected using a random surveillance strategy in midwestern Brazil: A comparison of ELISA and a rapid diagnostic test. - Marco Andrey C Frade; Natália A de Paula; Ciro M Gomes; Sebastian Vernal; Fred Bernardes Filho; Helena B Lugão; Marilda M M de Abreu; Patrícia Botini; Malcolm S Duthie; John S Spencer; Rosa Castália F R Soares; Norma T Foss (Public Library of Science (PLoS), 2017)
BACKGROUND:Leprosy diagnosis is mainly based on clinical evaluation, although this approach is difficult, especially for untrained physicians. We conducted a temporary campaign to detect previously unknown leprosy cases in midwestern Brazil and to compare the performance of different serological tests. METHODS:A mobile clinic was stationed at the main bus terminal in Brasília, Brazil. Volunteers were quizzed and given a clinical exam to allow categorization as either patients, known contacts of patients or non-contacts, and blood was collected to determine anti-PGL-I and anti-LID-1 antibody titers by ELISA and by the NDO-LID rapid test. New cases of leprosy and the impact of performing this broad random surveillance strategy were evaluated. Accuracy values and concordance between the test results were evaluated among all groups. RESULTS:Four hundred thirty-four individuals were evaluated, and 44 (10.1%) were diagnosed with leprosy. Borderline forms were the most frequent presentation. Both tests presented higher positivity in those individuals with multibacillary disease. Serological tests demonstrated specificities arround 70% for anti-PGL-1 and anti-LID ELISA; and arround 40% for NDO-LID. Sensitivities ranged from 48 to 62%. A substantial agreement between NDO-LID and ELISA with concomitant positive results was found within leprosy patients (Kappa index = 0.79 CI95% 0.36-1.22). CONCLUSIONS:The unexpectedly high leprosy prevalence in this population indicates ongoing community-based exposure to Mycobacterium leprae antigens and high rates of subclinical infection. All tests showed low specificity and sensitivity values and therefore cannot be considered for use as stand-alone diagnostics. Rather, considering their positivity among MB patients and non-patients, these tests can be considered effective tools for screening and identifying individuals at high risk who might benefit from regular monitoring.